2008
DOI: 10.1007/s00737-008-0219-y
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change in depressive symptoms from pregnancy to two months postpartum in childbearing immigrant women

Abstract: The present study explored changes in mental health and functional status from pregnancy to 2 months postpartum in a sample of 106 childbearing immigrant women. Three sets of variables were examined in relation to postpartum depressive symptomatology: (1) prenatal depression, worries, and somatic symptoms; (2) social relationships (marital quality and social support), and (3) factors related to migration (premigration stress and length of stay in the host country). We found that 37.7% of the women in this comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 45 publications
9
93
0
8
Order By: Relevance
“…A recent large-scale Canadian study 1 reported all immigrants had an increased risk for prenatal depression, compared with Canadian-born women (30% and 23%, respectively). Likewise, 2 smaller-scale Canadian studies 40,41 reported extremely high rates of antenatal depression (38% to 42%) in immigrant women, using the same cut-off score of 12 on the EPDS. Discrepancies may be related to differing study populations.…”
Section: Rates and Correlates Of Prenatal Depressive Symptomsmentioning
confidence: 97%
“…A recent large-scale Canadian study 1 reported all immigrants had an increased risk for prenatal depression, compared with Canadian-born women (30% and 23%, respectively). Likewise, 2 smaller-scale Canadian studies 40,41 reported extremely high rates of antenatal depression (38% to 42%) in immigrant women, using the same cut-off score of 12 on the EPDS. Discrepancies may be related to differing study populations.…”
Section: Rates and Correlates Of Prenatal Depressive Symptomsmentioning
confidence: 97%
“…Dysfunctional beliefs and self-esteem (Jones et al, 2010), as well as quality of the relationship as a couple (Zelkowitz et al, 2008), and life events (Rubertsson et al, 2005) can all increase the risk of developing postnatal depression. There are numerous studies which specifically analyse the effect that anxiety and depressive disorders during pregnancy have on postnatal depression. The presence of depressive symptoms during pregnancy has been associated with the onset of depression after childbirth (Chaudron et al, 2001;Milgrom et al, 2008;Saisto, Salmela-Aro, Nurmi, and Halmesmaki, 2001).…”
Section: Emotional Elements Personality and Postnatal Depressionmentioning
confidence: 99%
“…However, these women have difficulty getting their mental health care needs met (Donnelly, 2004;Morrow & Chappell, 1999;O'Mahony & Donnelly, 2007a, 2007b. Barriers influencing immigrant and refugee women's mental health care include low socioeconomic status (Chiu, Ganesan, Clark, & Morrow, 2005;Dhooper & Tran, 1998;Pilowsky, 1991;Zelkowitz et al, 2008), unemployment and underemployment (Beiser, Johnson, & Turner, 1993;Bhui et al, 2003;Thompson, 2000), marginalization, 279 280 T. T. DONNELLY ET AL. discrimination, gender issues, language barriers (Chiu et al, 2005;Dhooper & Tran, 1998;O'Mahony & Donnelly, 2007b;Ziguras, Stankovska, & Minas, 1999), cultural differences (Anderson, 1987a;Dhooper & Tran, 1998;Li & Browne, 2000;O'Mahony & Donnelly, 2007a), social stigma, and lack of knowledge regarding available mental health care services (Chiu et al, 2005;O'Mahony & Donnelly, 2007a, 2007b.…”
mentioning
confidence: 99%